The active participation of the Greater Mothers of the Hospital of Santo Christ of the Pains (Pozo Santo) under the administration of the Fraternity of the Mercy of Seville - Paula Ermila Rivasplata Varillas (Universidad de Alicante, 2017)
The major mother of the Holy Well hospital-sanctorum fulfilled a transcendental paper in the maintenance of that institution. Even exceeded its functions, proposing, suggesting and making proposals even without the permission of his patronage that was the Brotherhood of the Mercy that was directing the Pious House of analogous name. The free interference of the major mother in the management of Holly Well often allowed by the Mercy provoked for the bishopric the first problem of consideration as the dismissal of the major mother Feliciana of Holy Teresa and chaplain at the request of vicar the Brotherhood of Mercy obeyed in 1737. However, soon after the incident, the same major mother proposed by the vicar resumed her leadership role absolutely necessary to maintain the Pozo Santo and the brotherhood of Mercy understood and accepted.